Penggunaan Media Papan Berhitung Pada Pembelajaran Matematika Untuk Siswa Kelas II SDN 6 Wonogiri - Ratana, Bodhi (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2023)
Mathematics is a natural science that has an important role in the development of science and technology. Many learners in school view maths as the most difficult subject. In fact, until now there are still students who are less interested in mathematics and the results of learning mathematics have not shown optimal results. This type of research is Research and Development (R&D), which is research to produce new products or perfect existing products. that the counting board product is